Adsorption properties of the fumed individual and mixed Si, Ti and Al oxides as proxies for the Antarctic atmospheric mineral aerosols - Bazylevska, M.S.; Bogillo, V.I. (Український антарктичний журнал, 2019)
The aim of the study is to determine the effects of structure and content of X, CX in the oxides X/SiO₂ (X = Al₂O₃, TiO₂, Al₂O₃/TiO₂) on the surface characteristics. The low-temperature nitrogen adsorption isotherms on the surface of 12 individual and mixed fumed oxides of Si, Ti and Al, as proxies for the Antarctic atmospheric mineral aerosols, were measured by volumetric method. Метою роботи було визначення впливу природи та вмісту X, CX в оксидах X/SiO₂ (X = Al₂O₃, TiO₂, Al₂O₃/ TiO₂) на характеристики їх поверхні. Методом волюметрії виміряні низькотемпературні ізотерми адсорбції азоту на поверхні 12 індивідуальних і змішаних пірогених оксидів Si, Ti та Al, як компонентів мінеральних аерозолів в атмосфері Антарктики.